AFIRMASI POSITIF SEBAGAI INTERVENSI KETIDAKBERDAYAAN PADA MASALAH KESEHATAN PERKOTAANSYSTEMIC LUPUS ERYTHEMATOSUS - Salwa Muniroh; Ice Yulia Wardani (Jurnal Ilmu Keperawatan Jiwa, 2018)
POSITIVE AFFIRMATION AS AN INTERVENTION OF INEQUALITY IN URBAN SYSTEMIC LUPUS ERYTHEMATOSUS PROBLEMS Environmental damage that occurs in urban areas can lead to a variety of health problems. One health problem that has a higher risk in cities is Systemic Lupus Erythematosus (SLE). SLE can cause psychosocial problems, one of which is powerless. SLE can also affect the patient's relationship with the family or the closest person. The Final Scientific Work Ners aims to describe nursing care with problems of helplessness in patients and families of patients with SLE. The author carries out nursing care that focuses on helplessness and decreases in family coping for eight days. Evaluation results indicate that signs and symptoms helplessness in patients has diminished. However, the deteriorating condition of Mr. S's disease caused the problem to reappear. On the other hand, the patient's family is better able to care for the patient.